Glucose-assisted reduction achieved transparent p-type cuprous oxide thin film by a solution method. (2nd September 2016) - Nie, Sha; Sun, Jian; Gong, Hao; Chen, Zequn; Huang, Yifei; Xu, Jianmei; Zhao, Ling; Zhou, Wei; Wang, Qing
Abstract: The fabrication of p -type cuprous oxide thin film via a cheap and simple chemical method has been known as challenging. We first find that glucose can assist reduce Cu to a lower valence state in the preparation of cuprous oxide films by the sol-gel method. By first adding glucose in the sol as reducing agent, oxidation from the oxygen in the environment is limited and transparent p -type cuprous oxide films are eventually achieved under optimized experimental conditions. We have developed a p -type cuprous oxide thin film with an optimal Hall mobility of ∼8 cm 2 /Vs and an optical transmittance of 78%.